Cooperative mechanisms of oxygen vacancy stabilization and migration in the isolated tetrahedral anion Scheelite structure - Xiaoyan Yang (Nature Portfolio, 2018)
Fast oxide ion conductors are the key materials for some technological devices. Here the authors report the creation and stabilization of oxygen vacancies in BiVO4 Scheelite with isolated tetrahedral anion structures for improved ionic conducting performance and understanding of the conduction mechanism.